Two new species of Bulbophyllum (Orchidaceae) from Thailand - Vermeulen, Jaap J. (2021)
Two new species of Bulbophyllum (Orchidaceae) are described: B. sphenoglossum (sect. Lemniscata) and B. trigonanthum (sect. Reptantia). Both species occur in Thailand.